2014
DOI: 10.1136/fetalneonatal-2013-305665
|View full text |Cite
|
Sign up to set email alerts
|

Bi-level CPAP does not improve gas exchange when compared with conventional CPAP for the treatment of neonates recovering from respiratory distress syndrome

Abstract: AimWe hypothesised that short-term application of bilevel nasal continuous positive airway pressure CPAP (SiPAP) compared with conventional nasal CPAP (nCPAP) at the same mean airway pressure in infants with persistent oxygen need recovering from respiratory distress syndrome would improve CO 2 removal with no change in oxygen requirement. Design Non-blinded, randomised, observational fourperiod crossover study. Setting/population Level III NICU; low-birthweight infants requiring CPAP and oxygen while recoveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
(11 reference statements)
0
18
0
Order By: Relevance
“…Nineteen of them had previous intubation and mechanical ventilation and were at an average 33 days of age. The authors compared CPAP and BiPAP in the same patient for a period of one hour and found that BiPAP didn´t improve removal of CO 2 , oxygenation and other physiological parameters [15]. Non-invasive ventilation has also being used for moderate RDS.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen of them had previous intubation and mechanical ventilation and were at an average 33 days of age. The authors compared CPAP and BiPAP in the same patient for a period of one hour and found that BiPAP didn´t improve removal of CO 2 , oxygenation and other physiological parameters [15]. Non-invasive ventilation has also being used for moderate RDS.…”
Section: Discussionmentioning
confidence: 99%
“…These are typically delivered through CPAP flow driver devices and generate low PIP of about 9–11 cm H 2 O generally using fairly low rates of around 20 and long inspiratory times of about 0.8 s. Although popular, there is no evidence that BIPAP confers any advantage over CPAP, and any clinical differences may simply reflect a higher overall mean airway pressure [97]. Modern ventilators with flow and pressure sensors also provide nasal intermittent positive pressure ventilation, or NIPPV, using pressures similar to those used for invasive MV.…”
Section: Non-invasive Respiratory Supportmentioning
confidence: 99%
“…It is unclear whether these equate to changes in tidal volume or simply an overall increase in the CPAP level. Although increasingly popular, there is not much evidence that it confers any significant advantage over CPAP [84,85]. …”
Section: Non-invasive Respiratory Supportmentioning
confidence: 99%